Leadership Style And Motivation Work For Nursing Staff In The Internal Eletive Unit With Emergency Hospital National Guido Valadares Dili Timor-Leste 2023 - Ximenes da Conceição, José; de Jesus Vaz Cabral, Teresa; Guterres Pereira, Acacio; Oqui, Maximiano; dos Santos, Julito; Dores Xavier Amaral, Celenciana das (Jurnal Syntax Fusion, 2023)
According to research findings Maria Kontesa (2014), conducting a survey on Leadership style and Nursing Work Motivation in the Treatment Room of the General Hospital Dr. Rasiding Padang. As a result, the head of nursing used a democratic leadership style with a percentage (44.7%), otocratic with a percentage (34.2%), participatory with a percentage (18.4%), local government with a percentage (2.6%). And the motivation of nursing services was sufficient (44.1%), the motivation was high (38.4%), the motivation was low (17.6%). According to the source of human resources statistics, HNGV, 2022. The data on the assessment of leadership services and the motivation of nursing services at the Guido Valadares National Hospital, (2020-2021) shows that very good 576, good 70%, sufficient 15% and insufficient 0%. Based on the results of the survey on the distribution of respondents based on leadership style in the Department of Internal Elektiva and Emergency HNGV, the majority of respondents were 14 with (35%), and the majority were 26 with (65%). The results of the analysis of the statistical correlation test of the spearman. The significant value P value =.01 is lower than the value of 0,5 means that there is a significant relationship between the leadership style and the work motivation of the nursing staff and the results of the correlation value r = 0,554b which is located between 0,0,0-0,599 categories of strong correlation enough with the positive relationship (+).